2021
DOI: 10.1080/00472778.2021.1934849
|View full text |Cite
|
Sign up to set email alerts
|

The why and the how: A nexus on how opportunity, risk and personality affect entrepreneurial intention

Abstract: Opportunity-recognition, risk-taking and personality traits are central person-oriented characteristics for entrepreneurial intention. Despite the fact that various explanations have been proposed on how they affect entrepreneurial intention, it is still unclear which explanation is the most forceful one. This study compares three explanatory mechanisms and reveals that a newly derived trait−opportunity−risk nexus explains best why individuals intend to become entrepreneurs. The nexus was tested with 412 emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 86 publications
(112 reference statements)
0
15
0
2
Order By: Relevance
“…In addition, risk-taking companies tend to operate in the context of information sharing and learning together, so they can improve their knowledge and identify opportunities faster than their competitors [73]. A sense of regret for missing a profit opportunity serves to encourage people to take risks, thereby increasing their entrepreneurial intentions [1].…”
Section: Risk Tolerance Capacity (Rtc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, risk-taking companies tend to operate in the context of information sharing and learning together, so they can improve their knowledge and identify opportunities faster than their competitors [73]. A sense of regret for missing a profit opportunity serves to encourage people to take risks, thereby increasing their entrepreneurial intentions [1].…”
Section: Risk Tolerance Capacity (Rtc)mentioning
confidence: 99%
“…In view of the benefits of entrepreneurship, it has led to innovative new enterprises and job creation, which is considered one of the most effective ways to increase competition and shape markets, stimulating long-term growth and getting rid of poverty [1,2]. Entrepreneurship is not only an essential driving force of social health and wealth but also a powerful engine of economic growth [3] and technological progress in all countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Shane (2000) found that entrepreneurs saw opportunities within new technology based on their expertise and different people would come up with different ideas depending upon their backgrounds. More recently, scholars have found that personality and attitudes toward risk taking also influence entrepreneurial intentions (Bergner et al, 2021). The Austrian process of opportunity recognition is different than what would be predicted by neoclassical theory which implies that entrepreneurs base their decisions solely on market inefficacies and price.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of social cognitive theory in entrepreneurship, the social and economic environment influences the attitude of the individuals through personal perceptions ( Bacq et al, 2016 ). Moreover, perceptions are formed in the shape of unsafe and risky environments that affect individuals’ entrepreneurial intention to become entrepreneurs ( Bergner et al, 2021 ). Ghosh (2018) suggests that terrorism attacks, neutral disasters, and uncertain environments harm countries’ growth and new business development activities.…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%